Decision-Making for Managing Climate-Related Risks: Unpacking the Decision Process to Avoid “Trial-and-Error” Responses - Constable, Andrew J.; French, Simon; Karoblyte, Vita; Viner, David (Frontiers in Climate, 2022)
We provide an overview of decision support tools and methods that are available for managing climate-related risks and for delivering adaptation and resilience options and solutions. The importance of understanding political, socio-economic and cultural contexts and the decision processes that these tools support is emphasised. No tool or method is universally suited to all circumstances. Some decision processes are structured with formal governance requirements; while others are less so. In all cases, discussions and interactions with stakeholders and other players will have formal and informal aspects. We categorise decision support tools in several broad ways with the aim of helping decision makers and their advisors select tools that are appropriate to their culture, resources and other circumstances. The assessment examines the constraints and methodological assumptions that need be considered.